A Case Study of Intractable Diarrhea Due to Neonatal Microvillous Inclusion Disease. (4th July 2017) - Bulut, Ozgul; Ahishali, Bulent; Gulluoglu, Mine; Arslanoglu, Sertac
ABSTRACT: Background: Microvillous inclusion disease (MVID) is one of the most severe congenital diarrhea disorders, caused by a genetic defect in enterocyte differentiation and polarization. Case report: We describe a neonate who presented with severe weight loss, hypernatremic dehydration and metabolic acidosis due to intractable diarrhea due to MVID, confirmed by electron microscopy. Conclusion: MVID can present with severe weight loss, hypernatremic dehydration and metabolic acidosis that is life threatening. The diagnosis is made by typical findings on light microscopy and electron microscope of small bowel biopsies. The only therapeutic options at this time are total parenteral nutrition and bowel rest and intestinal transplantation.